Bioarqueologia dos povos Tapuia: o caso do sítio funerário Pedra da Tesoura, Boqueirão-PB, Brasil - Moraes, Flávio Augusto de Aguiar (2021)
The interpretative possibilities of the funerary environment, spatially arising from an archaeological context, are numerous. However, it is necessary to use appropriate methods so that there is no loss of information in the data collection process, both in the field and in the laboratory. This research uses osteological material from the Pedra da Tesoura site, with a chronology of 1,470 ± 30 A.P. (Beta-543287), located in the city of Boqueirão, in the Cariri region of Paraíba. The methodology used in turn was that of bio-archaeology, in line with archeotanatology. We sought to establish the NMI, estimated age at death, sex, and possible paleopathologies. Therefore, this work aims to discuss the specifics of a funerary site, presenting the different forms of burial, and using the deposition context and funerary gestures as variables. The site is a shelter under-rock and is characterized by having a room of about 12m², with a thin layer of sediment, not exceeding 30cm in depth, reaching from there the matrix rock or large blocks. In this place, the presence of at least four structures of secondary burials was identified, being three multiples with cremation traces and one burial bundle with bones showing red pigment. The NMI indicated the existence of twenty-four individuals, thirteen adults and eleven non-adults. The sex designation was limited due to the low degree of preservation of bone material, especially those found in context. With regard to the results of the paleopathological analysis, a predominance of degenerative joint pathologies was identified. The ethnohistorical information available in the documents and works of chroniclers indicate that the region where the Pedra da Tesoura site is located was densely occupied by peoples designated as Tapuia. In spite of the fact of the significant chronological interval between the dating obtained and the dates of realization of the etihistorical writings, such information helps to reflect on the evidence found.